Identification of Invasive Understolans in Nganggring Tourism Village, Girikerto Village, Sleman Regency, Special Region of Yogyakarta - Alvina Novelinda Kusuma; Fikri Arkan Maulana; Sa’ad Abdul Jabbar; Lia Kusumaningrum (Jurnal Ilmu Ilmu Kehutanan, 2024)
Abstract: This study identifies and analyzes invasive understory plants posing a threat to the ecological balance in Nganggring Village, Sleman, Yogyakarta Special Region, particularly within the prominent Salak Pondoh plantation. Employing direct observation and interpreting remote sensing imagery from Google Earth, the research collected data using a systematic grid approach at intervals of 10x10 and 5x5 meters. The findings reveal the presence of various invasive species, including Legetan, Elephant Grass, Thunbergia erecta, Israeli Grass, and others. These plants exhibit high adaptability, rapid growth, and competitive capabilities, posing a significant risk to the local ecosystem. The study provides insights into the diversity of invasive understory plants in Nganggring Village, serving as a foundational step in minimizing adverse environmental impacts. Sustainable environmental protection and management efforts are crucial for mitigating invasion risks and preserving ecological balance in the region. This research contributes to a better understanding of invasive flora, supporting environmental sustainability amid the prominent Salak Pondoh plantation.